Spatial resources in pre-service teachers’ instructional practices in VR tandems: co-constructing shared spaces and embodied spatial scaffolding - Lazovic, Milica (Frontiers in Communication, 2025)
This study examines the use of spatial resources in instructional practices during virtual reality (VR) tandem interactions between pre-service teachers of German as a foreign language and learners with A2 language proficiency. These interactions take place within the highly immersive virtual environment Wander, designed to facilitate (inter)cultural learning. The linguistic, perceptual, epistemological, and technical asymmetries within this setting necessitate scaffolding the co-participant through the virtual environment, guiding them in spatial exploration, orienting them to usability cues, leveraging spatial resources to support interactive and learning processes, developing embodied practices, and fostering mutual alignment. The analysis focuses on pre-service teachers’ use of spatial resources and their practices of embodied spatial scaffolding to support learning in three key areas: instructing on app functionality, developing new embodied action patterns, and fostering a functional understanding of virtual objects. Prior to this, the study examines the instructional grounding for upcoming actions, such as directing instructions, by focusing on two key aspects: the co-construction of shared focus and the alignment of perspectives. This is achieved through eliciting, monitoring, and adjusting according to the position of the co-participant’s avatar in situations of dynamic spatial perception. These situations are characterized by the interplay between changing position, orientation, and floating attention in the context of exploratory spatial navigation, the presence of distractors, or transitions. Methodologically, this study is grounded in conversation analysis and interactional linguistics. Video recordings capture participants’ perspectives in a split-screen format, documenting parallel perspectivization in action flow and revealing shifts in interactional coordination. The results indicate, among other things, that participants prefer using pointing gestures accompanied by local adverbs, which are semantically subsequently extended, specified, varied, or reduced in a scaffolded way. Over time, synchronized co-referencing practices involving joint and matched pointing become central to negotiating a blended origo. The sequential analysis identifies meta-regulatory practices for perspective alignment by eliciting the other’s perspective and monitoring the co-participants’ avatar orientation and spatial relation to align for goal-directed action before co-constructing the focus. This study contributes to the understanding of immersive instruction in virtual learning environments by highlighting key aspects such as pre-instructional spatial self-and other-monitoring activities designed to support spatial self-alignment. Embodied spatial scaffolding involves some of the following supporting aspects: the adjustment of the internal spatial interface, the transition from static to dynamic interaction within the virtual environment, the management of spatial relations (explorative vs. concrete references), the control of spatial interaction and coherence, the orientation to calls for alignment, the bridging of spatial transformations in the action flow, and the monitoring of the co-participants’ avatar. The interactions tend to emphasize spatial engagement, with participants sometimes “overdoing” spatial elements rather than using spatial cues to develop more complex interactions.